Global carbon dioxide efflux from rivers enhanced by high nocturnal emissions - Gómez-Gener, Lluís; Rocher-Ros, Gerard; Battin, Tom; Cohen, Matthew J.; Dalmagro, Higo J.; Dinsmore, Kerry J.; Drake, Travis W.; Duvert, Clément; Enrich-Prast, Alex; Horgby, Åsa; Johnson, Mark S.; Kirk, Lily; et al. (Nature geoscience, 2021)
Carbon dioxide (CO 2 ) emissions to the atmosphere from running waters are estimated to be four times greater than the total carbon (C) flux to the oceans. However, these fluxes remain poorly constrained because of substantial spatial and temporal variability in dissolved CO 2 concentrations. Using a global compilation of high-frequency CO 2 measurements, we demonstrate that nocturnal CO 2 emissions are on average 27% (0.9 gC m −2 d −1 ) greater than those estimated from diurnal concentrations alone. Constraints on light availability due to canopy shading or water colour are the principal controls on observed diel (24 hour) variation, suggesting this nocturnal increase arises from daytime fixation of CO 2 by photosynthesis. Because current global estimates of CO 2 emissions to the atmosphere from running waters (0.65–1.8 PgC yr −1 ) rely primarily on discrete measurements of dissolved CO 2 obtained during the day, they substantially underestimate the magnitude of this flux. Accounting for night-time CO 2 emissions may elevate global estimates from running waters to the atmosphere by 0.20–0.55 PgC yr −1 . Failing to account for emission differences between day and night will lead to an underestimate of global CO 2 emissions from rivers by up to 0.55 PgC yr –1 , according to analyses of high-frequency CO 2 measurements.